« Nouvelles migrations » au Brésil : des représentations de l’accueil aux formes contemporaines de racisme - Marie-Caroline Saglio-Yatzimirsky; Ana Gebrim (Brésil(s), 2017)
Since 2010, Brazil has been receiving new political migrations, particularly from Haiti, sub-Saharan Africa, Syria and South Asia. This article analyzes how these refugees have resettled in the city of São Paulo. Some have experienced violent expressions of racism, leading to the prospect that the presence of these new populations interrogates not only Brazilian society, historically structured by social markers, but also urban sociabilities and subjectivities.